Family Power and Corporate Investment Efficiency - Ahmed, Al-Hadi; Eulaiwi, Baban; Duong, Lien; Taylor, Grantley; Dutta, Saurav (Taylor & Francis, 2022)
This study examines the relationship between family power and corporate investment efficiency in Gulf Cooperative Council (GCC) countries. Family power in firms is manifested in how much decision-making power is concentrated in the hands of family members who are active either on the board of directors, or as executives of a firm. Using a unique measure of “family power,” we contribute to a growing interest in the role of family influence in the GCC emerging markets, where firms and business practices are typically controlled by families. We find that increased family power reduces firms’ level of under- and over-investment. We assert that this relation arises because firms are able to exhibit high levels of family power through socioemotional wealth preservation in reducing both management agency costs and earnings management.